Socialization of the Use of Semantic Scholar in Improving the Quality of Student in Indonesia: Pengabdian - Sumardi; Nadiya Yunan; Dasep Supriatna; Irwan Faizal; Petrus Jhon Alfred D.D. (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The author conducted this outreach program over a two-week period for the students he teaches on campus especially student in Universitas Pancasakti Makassar, Universitas Widya Gama Mahakam Samarinda, STITNU Al-Farabi Pangandaran, Politeknik Penerbangan Indonesia Curug, and Universitas Islam Negeri Antasari Banjarmasin. The author expresses his deepest gratitude to the students who were willing to participate in the socialization regarding semantic scholars in improving the quality of student research. There were one hundred and fifty students from five campuses: Pancasakti Makassar, Widya Gama Mahakam University Samarinda, STITNU Al-Farabi Pangandaran, Indonesian Aviation Polytechnic Curug, and Antasari State Islamic University Banjarmasin. The author sincerely hopes that after this, the quality of student research can further improve.